The Relevance of Jamal al-Din al-Afghani's and Muhammad Abduh's Educational Thought to Contemporary Education - Syamzan Syukur; Maswan Ahmadi; Susmihara Susmihara (Yayasan Rahmat Islamiyah, 2026)
This study examines the educational philosophy of 19th-century Islamic modernist reformers Jamal al-Din al-Afghani and Muhammad Abduh, analyzing its enduring relevance to contemporary educational challenges. Modern educational systems—particularly within Muslim-majority societies—frequently grapple with epistemological dualism, pedagogical dogmatism, and a structural gap between traditional moral formation and rapid scientific-technological advancement. Utilizing a qualitative philosophical inquiry and historical-hermeneutic content analysis, this paper systematically evaluates Afghani's anti-colonial, socio-political educational awakening alongside Abduh's institutional and curricular reform paradigms at Al-Azhar. The findings reveal that both thinkers formulated a revolutionary synthesis that rejected taqlid (uncritical imitation), advocated for the revival of ijtihad (independent reasoning), and championed the integration of modern empirical sciences with dynamic Islamic ethics. The study demonstrates that al-Afghani's emphasis on critical political consciousness and Abduh's structural integration of sacred and secular knowledge offer vital theoretical models for resolving contemporary epistemological bifurcation, combating instructional passivity, and cultivating ethically grounded, critically minded citizens capable of navigating globalized knowledge economies.